2006
DOI: 10.1038/sj.leu.2404489
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells inhibit proliferation and apoptosis of tumor cells: impact on in vivo tumor growth

Abstract: Mesenchymal stem cells (MSC) have received much attention in the field of hematopoietic stem cell transplantation because not only do they support hematopoiesis but also exhibit a profound immunosuppressive activity that can be exploited to prevent undesired alloreactivity. We have previously shown that their immunosuppressive activity is mainly exerted at the level of T-cell proliferation. Here, we show that MSC exhibit a similar antiproliferative activity on tumor cells of hematopoietic and non hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
319
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(347 citation statements)
references
References 31 publications
25
319
2
1
Order By: Relevance
“…Thus, human and mMSCs can home to tumor sites and inhibit the growth of neoplastic cells as shown in models of gliomas [103], Kaposi's sarcomas [104] and hepatoma [105,106]. Other study shows that hMSCs exhibit an antiproliferative activity on tumor cells, although in in-vivo experiments, the co-injection of MSCs caused an increase in tumor cell growth rate [107].…”
Section: Mscs and Tumor Growthmentioning
confidence: 99%
“…Thus, human and mMSCs can home to tumor sites and inhibit the growth of neoplastic cells as shown in models of gliomas [103], Kaposi's sarcomas [104] and hepatoma [105,106]. Other study shows that hMSCs exhibit an antiproliferative activity on tumor cells, although in in-vivo experiments, the co-injection of MSCs caused an increase in tumor cell growth rate [107].…”
Section: Mscs and Tumor Growthmentioning
confidence: 99%
“…However, the overall role of MSC in the tumor microenvironment remains controversial. Although on the one hand, MSC can provide survival, growth and drug resistance signals, 48,54 MSC can also induce cell cycle and growth arrest in epithelial cancer [55][56][57] and leukemia cells. 58 On the basis of these findings, the therapeutic use of MSC to decelerate tumor growth has been proposed.…”
Section: Cxcr4: a Unique Chemokine Receptormentioning
confidence: 99%
“…However, apart from one publication reporting of MSC-induced apoptosis of proliferating lymphocytes, 36 most publications not only excluded the involvement of MSC-induced apoptosis of target cells but, in contrast, suggested that the arrest of apoptosis may be a major mechanism for MSCs imparting a survival signal to immune cells 28,37 as well as to other cells. 38 Clearly, a major mechanism leading to the inhibition of immune-cell effector functions is the arrest of the cell cycle in G0/G1, which results in the inhibition of cell proliferation. [26][27][28]38 Whether this effect is mediated by cell contact mechanisms or soluble factors is still not fully understood.…”
Section: Mechanisms Of Inhibition Of the Immune Responsementioning
confidence: 99%
“…38 Clearly, a major mechanism leading to the inhibition of immune-cell effector functions is the arrest of the cell cycle in G0/G1, which results in the inhibition of cell proliferation. [26][27][28]38 Whether this effect is mediated by cell contact mechanisms or soluble factors is still not fully understood. However, transwell experiments have shown putative paracrine soluble factors (Table 1) including hepatocyte growth factor (HGF) and transforming growth factor-b1 (TGF-b1), 22 prostaglandin E 2 39,30 indoleamine 2,3-deoxygenase, 40 inducible NO synthetase resulting in Stat 5 inhibition in lymphocytes, 41 soluble HLA-G 42 and soluble IL-1 receptor.…”
Section: Mechanisms Of Inhibition Of the Immune Responsementioning
confidence: 99%